Propagation of truth: or, "Tyranny anatomized" in four letter to the President of the United Stated ... with a few marginal notes ... - Lovell, James ((Early American Imprints. Second series ; no. 15453)., 1808)
To the President of the United States -- A late senator of Massachusetts -- The president of Harvard University -- The undergraduates thereof.